Aural Hematomas in Small Ruminants – Clinical Features, Surgical Treatment and Outcome - Câmara, Antonio Carlos Lopes; Amorim, Haiane Arruda Luz; Campebell, Rita de Cássia; Borges, José Renato Junqueira (Acta Scientiae Veterinariae, 2023)
Background: Aural or auricular hematoma is an important and prevalent surgical condition in small animals practice, and commonly reported in companion pets. The condition is characterized by blood accumulation between the pinnae’s dermal surface and the underlying perichondrium. In farm animals, most cases present surgical treatment with drainage of serosanguineous fluid from acute cases with clinical evolution ranging from 1 to 5 days. Therefore, the present work reports the clinical features, surgical treatment and outcome of aural hematomas in 3 small ruminants with a chronic evolution (7 to 20 days), detailing the post-surgical complications, such as wound infection and recurrence, and final cosmetic appearance of the pinnae. Cases: Upon physical examination, all animals were alert and presenting a good body condition score. Clinical alteration was restricted to a bilateral (Case 1) or unilateral (Cases 2 & 3) painless, and fluid-filled swelling, presenting doughy consistency masses within the fluid during pinna manipulation. The fluid-filled swellings were located on the concave (Case 1 - left ear & Case 2) and convex (Case 1 - right ear & Case 3) surface of the pinna. No primary pruritic disorders of the pinna were detected, and a diagnosis of traumatic aural hematoma was proposed. Due to the chronicity of the cases, surgical approach was advisable. The small ruminants underwent general anesthesia, and a linear incision over the skin overlying the hematoma was performed (Cases 1 & 2). After removal of blood and fibrin clots, the cavity was flushed and captonated 0 nylon mattress sutures were performed on either side of the incision, in order to obliterate the dead space. Due to recurrence after 14 days, Case 2 was submitted to a modified surgical approach using a S-shaped incision combined to multiple drainage holes (MDH) using a disposable 6 mm biopsy punch. The same approach has performed in Case 3. Then, 0 nylon mattress sutures followed by a tight protective pressure and absorbent bandage combined with an Elizabethan collar was applied. Postoperatively, Case 1 presented surgical site infection and the antibiotic was changed after bacterial culture and antibiogram results. Hospital discharge varied from 14 to 19 days’ post-surgery. All animals presented some degree of ear retraction and a linear or S-shaped scar on the affected ear, but final cosmetic appearance was satisfactory to all owners. Discussion: Aural or auricular hematomas are a frequent disorder in dogs and cats clinical practice. In sheep, the few reported cases have been associated with pruritic disorders of the pinna, such as ticks infestation and sarcoptic mange. Whilst in goats, traumatic injuries, such as ear tagging and trauma from others goats, are considered the main cause, especially in breeds with pendulous ear. In our cases with chronic evolution (> 7 days), the most important clinical feature was the presence of doughy consistency masses within the fluid, suggesting matured blood and fibrin clots. A linear incision with captonated 0 nylon mattress sutures was associated to post-surgical complications, such as wound infection and aural hematoma recurrence. Therefore, a S-shaped incision associated to creation of MDH, in order to achieve better drainage, was the chosen approach in the second surgery (Case 2) and on the subsequent patient (Case 3). To the best of our knowledge, this is the first report using the MDH approach in farm animals, that appears to be an effective treatment for chronic aural hematomas in small ruminants. Keywords: auricular hematoma, biopsy punch, goats, sheep.